A case report of endoscopic resection for the treatment of duodenal Brunner's gland adenoma with upper gastrointestinal bleeding. Issue 52 (24th December 2020) - Liang, Ma; Liwen, Zhang; Jianguo, Song; Juan, Dai; Ting, Shen; Jianping, Chen
Abstract: Rationale: Gastrointestinal bleeding as the first sign of Brunner's gland adenoma (BGA) is an extremely rare, and its clinical features and treatment methods have not been well described. Patient concerns: We described a 81-year-old female patient with coronary artery disease and chronic atrial fibrillation presenting with presenting with gastrointestinal bleeding requiring blood transfusion. Diagnoses: The diagnosis of our case mainly refered to radiologic imaging and endoscopic examination. Histological result was compatible with BGA. Interventions: This mass lesion (6 × 7 cm diameter) was successfully totally removed by endoscopic submucosal dissection (ESD) for more than three hours. Outcomes: The patient was followed up for 6 months to date without recurrence. Lessons: Endoscopic removal is considered as a safe and low-risk treatment for elderly patients with severe underlying diseases presenting with gastrointestinal bleeding.